People get rid of grass, but I grow it: Trong's story - International Livestock Research Institute (International Livestock Research Institute, 2022)
After two and half years of implementation (2019–2021), the ‘Livestock-led interventions towards equitable livelihoods and improved environment in the Northwest Highlands of Vietnam’ or Li-chăn project has resulted in agricultural system transformation in northwest Vietnam.